Examination of Traffic Incident Records and Development of a Rapid Incident Response Plan - Kabit, M.R; Charles, P.; Fereirra, L.; Hojati, A.T (PATREC, 2011)
Effective traffic incident management is an important success factor in reducing incident duration and the severe resultant congestion impacts. As such by having proper and reliable traffic incident indicators can greatly improve prioritisation and deployment of effective rapid incident response. This research aimed to examine and improve indicators for better incident prioritisation and development of rapid incident response plans for Australian conditions. A review of current practices in Australia as well as in other countries, especially the US, was undertaken to assess traffic incident management strengths and weaknesses as a benchmark for the analysis. An examination of traffic incident records in south east Queensland was undertaken using logistic regression. Based on the findings, a rapid incident management plan has been developed that can assist traffic management centres in Australia to manage and deploy more effective traffic incident response.